As transformações na música popular brasileira: um processo de branqueamento? - Silva, Patrícia Fatima Crepaldi Bento da (2008)
The present work has as objective to analyze the occured transformations in brazilian popular music being verified if and of that it forms occurred, the process of exclusion of the black population in this brazilian cultural segment, thus leading, Brazilian music to a whiteness process. We concentrate ourselves in the study of the official and registered history of the Bossa Nova, inside of the period of 1958 the 1968, as well as its disagreements, unfoldings and antagonisms, therefore this is officially the first musical movement to happen in Brazil and from it diverse changes in brazilian popular music had occurred and that they answer to the main questions proposals in this work. In the perspective of music as a social field, according to Pierre Bourdieu, we analyze brazilian popular music from the existing racial conflicts in its half one, using the concept of a market of symbolic goods that legitimize chosen its and that it perpetuates its choices through its instances of reproduction, thus pointing the gotten results that confirm our initial hypothesis